Effectiveness of Using Accounting Computer Applications in Accounting Learning - Ni Putu Rita Sintadevi; Made Ayu Jayanti Prita Utami; Upayana Wiguna Eka Saputra; Sedana Wibawa (LPPM Universitas Buddhi Dharma, 2024)
The development of information technology has brought significant changes in various aspects of life, including in the world of education and business. In the context of higher education, the use of accounting software such as Accurate has become an integral part of the modern accounting curriculum. This is in line with the demands of the world of work which increasingly relies on technology in daily accounting practices. According to a survey conducted by the Indonesian Accountants Association (IAI) in 2020, more than 80% of companies in Indonesia have adopted accounting software in their operations, with Accurate being one of the main choices of the Bali State Polytechnic, as one of the leading vocational education institutions in Indonesia, has integrated the use of Accurate in the Business Administration Department curriculum. This step was taken in response to industry needs and an effort to increase graduate competency in facing the digital era. However, although the use of Accurate has been implemented, there has been no comprehensive evaluation of its effectiveness in improving students' accounting understanding and skills.This research aims to measure the extent to which the use of Accurate contributes to increasing conceptual understanding, practical skills, and work readiness of students majoring in Business Administration. By involving 162 respondents and using quantitative methods, the collected questionnaire data was then processed using SPSS version 26 software. The results of this research indicate that theoretically, this research strengthens the argument about the importance of technology integration in accounting education while emphasizing the role of contextual factors such as teaching methods and infrastructure. This supports a holistic approach in accounting curriculum development that focuses not only on content but also on delivery methods and learning environments.